2016
DOI: 10.1016/j.jmb.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Selection Analysis of Bacteriophage φCbK Susceptibility in Caulobacter crescentus

Abstract: Classical molecular genetics uses stringent selective conditions to identify mutants with distinct phenotypic responses. Mutations giving rise to less pronounced phenotypes are often missed. However, to gain systems-level insights into complex genetic interaction networks requires genome-wide assignment of quantitative phenotypic traits. In this paper, we present a quantitative selection approach coupled with transposon sequencing (QS-TnSeq) to globally identify the cellular components that orchestrate suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 25 publications
2
72
0
Order By: Relevance
“…TnSeq couples hypersaturated transposon (Tn) mutagenesis with next-generation sequencing to profile changes in genome-wide insertion patterns occurring upon selection of large mutant pools (Christen et al., 2011, Christen et al., 2016). We constructed a himar-based Tn probe and generated large input mutant libraries encompassing several hundreds of thousands of insertion events (STAR Methods).…”
Section: Resultsmentioning
confidence: 99%
“…TnSeq couples hypersaturated transposon (Tn) mutagenesis with next-generation sequencing to profile changes in genome-wide insertion patterns occurring upon selection of large mutant pools (Christen et al., 2011, Christen et al., 2016). We constructed a himar-based Tn probe and generated large input mutant libraries encompassing several hundreds of thousands of insertion events (STAR Methods).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting strain expresses a bipolarly localized and truncated ZitP-GFP fusion protein and is viable (Hughes et al, 2010). Consistent with this result, genome-wide transposon insertion sequencing (Tn-Seq) revealed that ZitP is not essential for viability, but required for pilus biogenesis and motility (Christen et al, 2011, 2016; Hughes et al, 2010)(Mignolet et al, 2016). The predicted ZitP protein harbors an N-terminal zinc-finger domain (zinc_ribbon_5 or PF13719 superfamily, residues 1–37, henceforth ZnR, Figure 1B–C) and a trans-membrane segment (TM, residues 106–127) preceding the C-terminal DUF3426 (residues 128–245).…”
Section: Resultsmentioning
confidence: 75%
“…Here, we unearth a reciprocal, physical and conserved interaction between PopZ and the cytoplasmic N-terminal zinc-finger domain (ZnR) from ZitP (Hughes et al, 2010), a bifunctional and bipolar membrane protein whose C-terminal DUF3426 domain is required for polar pilus biogenesis (Mignolet et al, 2016)(Christen et al, 2016), but dispensable for motility. We locate the structural determinants governing PopZ•ZitP complex formation and we show that this interaction is required to control cytokinesis and centromere positioning from the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…As pili are necessary for infection by the lytic caulophage CbK (φCbK) (Skerker and Shapiro, 2000), we specifically sought mutants in pilus assembly factors encoded outside of the major pilus assembly cpa gene locus ( pilA-cpaA-K) (Christen et al, 2016; Skerker and Shapiro, 2000). To this end, we conducted himar1 -transposon ( Tn ) mutagenesis of wild-type ( WT ) Caulobacter in the presence of φCbK (see Methods) and recovered mutants with Tninsertions in CCNA_02298, renamed here zitP (z inc-finger targeting the poles) because of the pleiotropic roles detailed below, or in cpaM (CCNA_03552 ) (Figure 1C) (Marks et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we conducted himar1 -transposon ( Tn ) mutagenesis of wild-type ( WT ) Caulobacter in the presence of φCbK (see Methods) and recovered mutants with Tninsertions in CCNA_02298, renamed here zitP (z inc-finger targeting the poles) because of the pleiotropic roles detailed below, or in cpaM (CCNA_03552 ) (Figure 1C) (Marks et al, 2010). While both genes have previously been implicated in polar functions and their transcription is cell cycle-regulated (Christen et al, 2016; Fioravanti et al, 2013; Fumeaux et al, 2014; Hughes et al, 2010; McGrath et al, 2007), they are poorly characterized. The zitP gene is predicted to encode a 311-residue bitopic trans-membrane (TM) protein harbouring a CXXC-(X) 19 -CXXC motif that binds a zinc ion (zinc_ribbon_5 or PF13719 superfamily, residues 1-37) at the cytoplasmic N-terminus (Bergé et al, 2016) and a conserved domain-of-unknown function (DUF3426, residues 128-245) in the C-terminal region that is predicted to reside in the periplasm (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%